2015
DOI: 10.1136/bmjopen-2015-009075
|View full text |Cite
|
Sign up to set email alerts
|

Health risk of air pollution on people living with major chronic diseases: a Canadian population-based study

Abstract: ObjectivesThe objective of this study was to use health administrative and environmental data to quantify the effects of ambient air pollution on health service use among those with chronic diseases. We hypothesised that health service use would be higher among those with more exposure to air pollution as measured by the Air Quality Health Index (AQHI).SettingHealth administrative data was used to quantify health service use at the primary (physician office visits) and secondary (emergency department visits, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 21 publications
2
20
0
1
Order By: Relevance
“…However, the nature and intensity of health impacts are expected to depend on characteristics of the receptor population [ 16 , 17 , 21 ]. Research on vulnerability to ambient air pollution has identified subpopulations with increased susceptibility to the effects of PM; these include persons with chronic diseases [ 22 ], as well as older adults, children, and possibly those with lower education, income, and employment status [ 23 ]. Although PM of wildfire origin differs from ambient air pollution in composition and exposure patterns, current research suggests that elderly and young populations will also be especially vulnerable to wildfire-derived PM [ 16 , 17 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the nature and intensity of health impacts are expected to depend on characteristics of the receptor population [ 16 , 17 , 21 ]. Research on vulnerability to ambient air pollution has identified subpopulations with increased susceptibility to the effects of PM; these include persons with chronic diseases [ 22 ], as well as older adults, children, and possibly those with lower education, income, and employment status [ 23 ]. Although PM of wildfire origin differs from ambient air pollution in composition and exposure patterns, current research suggests that elderly and young populations will also be especially vulnerable to wildfire-derived PM [ 16 , 17 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Air pollution is also associated with the acute worsening of pre-existing asthma and chronic obstructive pulmonary disease (COPD) and with progression from asthma to COPD [4, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…Tseng et al ( 2013 ) demonstrated the effect of cold temperatures on the exacerbation of COPD, and Alahmari et al ( 2015 ) reported that high level of atmospheric pollution had independent effects on the physical activity of COPD patients. Air pollution also increased the incidence of outpatient visits due to COPD even after standardization of temperature (To et al 2015 ). These reports also suggested that air pollution had independent health impact on COPD and BA patients besides temperature.…”
Section: Discussionmentioning
confidence: 99%